Autoregressions in small samples, priors about observables and initial conditions - Marek Jarociński; Albert Marcet (European Central Bank (ECB), 2010)
We propose a benchmark prior for the estimation of vector autoregressions: a prior about initial growth rates of the modeled series. We first show that the Bayesian vs frequentist small sample bias controversy is driven by different default initial conditions. These initial conditions are usually arbitrary and our prior serves to replace them in an intuitive way. To implement this prior we develop a technique for translating priors about observables into priors about parameters. We find that our prior makes a big difference for the estimated persistence of output responses to monetary policy shocks in the United States.
Keywords: C11; C22; C32; 330; Bayesian estimation; Bias Correction; Initial Condition; monetary policy shocks; Prior about Growth Rate; Small Sample Distribution; Vector autoregression; Geldpolitik; Schock; Wirtschaftswachstum; VAR-Modell; USA